2011
DOI: 10.1308/147870811x13137608455019
|View full text |Cite
|
Sign up to set email alerts
|

Risk evaluation in cutaneous melanoma patients undergoing lymph node dissection: impact of POSSUM

Abstract: INTRODUCTION When lymphatic metastasis occurs, surgery is the primary treatment modality in melanoma patients. Depending on the tumour stage, patients receive a completion lymph node dissection (CLND) when a positive sentinel node is detected. Patients with clinically evident disease of the regional lymph nodes are recommended to undergo a therapeutic lymph node dissection (TLND). The aim of this study was to assess the morbidity of CLND and TLND and to evaluate the Physiological and Operative Severity Score f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
9
0
2
Order By: Relevance
“…In addition, it has been considered questionable whether the prognosis of patients treated with CLND after positive SLNB is superior to that in patients treated with TLND after occurrence of clinical nodal disease . Evidence from seven studies in this review confirms that no clear advantage for CLND can be established, although there is some evidence in its favour: five studies reported numerically higher survival rates or survival time for patients who underwent CLND, and one study reported significantly higher DSS . Moreover, one study reported significantly better OS for CLND vs. TLND in patients with tumour thickness of 1–4 mm, suggesting that certain patient subpopulations are more likely to benefit from this surgical procedure.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In addition, it has been considered questionable whether the prognosis of patients treated with CLND after positive SLNB is superior to that in patients treated with TLND after occurrence of clinical nodal disease . Evidence from seven studies in this review confirms that no clear advantage for CLND can be established, although there is some evidence in its favour: five studies reported numerically higher survival rates or survival time for patients who underwent CLND, and one study reported significantly higher DSS . Moreover, one study reported significantly better OS for CLND vs. TLND in patients with tumour thickness of 1–4 mm, suggesting that certain patient subpopulations are more likely to benefit from this surgical procedure.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, Egberts et al . reported longer OS for patients undergoing CLND vs. TLND (43 vs. 27 months) (Table a). The latter study also reported non‐significantly longer median progression‐free survival (PFS) for CLND vs. TLND.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The prevalence of complications and morbidity associated with dissection of RLNs can be high: 28-77%. [2][3][4][5][6][7][8] Groin dissections are typically associated with a higher prevalence of complications than axillary dissections. 2,[9][10][11][12] In 1992, Baas et al undertook a retrospective review of 151 consecutive groin dissections.…”
mentioning
confidence: 99%